Virtual Key Opinion Leaders: How AI-Generated Influencers Transform Communication Strategies - Hayati, Setiyo; Setiawati, Isti Budhi; Novrianto, L.M. (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid integration of artificial intelligence (AI) into communication strategies has catalyzed the emergence of virtual key opinion leaders (KOLs), also known as AI-generated influencers. These entities are reshaping the dynamics of marketing, audience engagement, and brand communication by offering cost efficiency, scalability, and narrative consistency. This study examines the transformative role of virtual KOLs through a qualitative, library-based approach that synthesizes scholarly works, industry reports, and conceptual frameworks. The findings highlight four central dimensions: authenticity and trust, emotional engagement and parasocial relationships, strategic message effectiveness, and the ethical, social, and cultural implications of AI-mediated influence. While AI influencers can simulate authenticity and foster parasocial bonds through anthropomorphism, their artificiality raises questions about credibility, transparency, and ethical responsibility. Data-driven personalization enhances message targeting but introduces privacy concerns and risks of manipulative persuasion. Additionally, the adaptability of virtual KOLs across cultural markets provides opportunities for global engagement, yet also risks cultural appropriation and algorithmic bias. The analysis underscores that trust and authenticity in AI influencers are socially constructed rather than experience-based, requiring careful narrative design and transparent practices. Ultimately, virtual KOLs represent both an opportunity and a challenge: they enhance efficiency and personalization in strategic communication but necessitate robust ethical frameworks to safeguard consumer trust and autonomy. By addressing these complexities, this research contributes to advancing theoretical discourse in communication studies while offering practical insights for marketing professionals navigating the evolving digital ecosystem.